ARCHITECTURAL ENGINEERING IN THE DIGITAL ERA: PARAMETRIC DESIGN AND STRUCTURAL RATIONALIZATION - Prabawasari, Veronika Widi; Takahashi, Haruto; Baharuddin, Faizal; Schneider, Anna (Journal of Moeslim Research Technik, 2026)
Architectural engineering in the digital era is increasingly shaped by parametric design methodologies that enable complex form generation and performance-driven optimization. Rapid advancements in computational tools have transformed design processes, yet a persistent gap remains between architectural exploration and structural rationalization, often resulting in inefficiencies and post-design adjustments. This study aims to develop an integrated computational framework that aligns parametric design with structural performance, ensuring that architectural forms are both innovative and structurally feasible. A computational design-based methodology was employed, combining parametric modeling, finite element analysis, and algorithmic optimization across representative architectural typologies. Iterative workflows were implemented to establish continuous feedback between geometric parameters and structural responses. Results indicate that integrated parametric-structural models achieve higher structural efficiency, reduced material consumption, and improved deformation control compared to conventional and non-integrated approaches. Statistical analysis confirms significant performance improvements, while case-based validation demonstrates strong alignment between simulated and expected structural behavior. Findings further reveal that real-time integration enhances design adaptability and decision-making efficiency. This study concludes that the integration of parametric design and structural rationalization represents a robust and scalable paradigm for contemporary architectural engineering, offering significant implications for sustainability, performance optimization, and interdisciplinary collaboration.